Economical cultivation system of microalgae Spirulina platensis for lipid production. Issue 1 (February 2021) - Palanisamy, K M; Paramasivam, P; Jayakumar, S; Maniam, G P; Rahim, M H A; Govindan, N
Abstract: The marine algae Spirulina platensis was cultured in a medium of palm oil mill effluent (POME) and the production of lipid in the biomass was optimized. Among 7 species Spirulina platensis was isolated from the marine sample which have greater lipid potential was collected from Pantai Teluk Cempedak, Kuantan which is located at East Coast region of Pahang state. At 28+2 °C, the maximum lipid content in the biomass harvested at the end of a 15 days batch culture was quantified with the following values of the experimental factors: POME concentration with (10%, 20% and 30%) (v/v) and light intensity (3, 000 lux, 4, 000 lux, 5, 000 lux). Under the optimized conditions with 20% of POME, the maximum dry mass concentration of the was 754.5 mg L −1 with lipid 34.5% production on day 13 of a batch culture, declining to ∼687 mg L −1 on day 15. At 5, 000 lux light intensities, the maximum yield obtained was 854.6 mg L −1 with lipid 35.8% production on day 14, it declined to 732.8 mg L −1 on day 15.